577 Daily facilitators and barriers to adolescent sleep: Contribution to actual sleep over 28-days of school and vacation. (3rd May 2021) - Maskevich, Svetlana; Shen, Lin; Wiley, Joshua; Drummond, Sean; Bei, Bei
Abstract: Introduction: Little is known about what adolescents perceive as helping (facilitators) or preventing (barriers) them from getting sufficient and good quality sleep, and how these factors contribute to their actual sleep. Methods: 205 (54.2% female, 64.4% non-white) Year 10–12 adolescents (Mage = 16.9 ± 0.9) completed daily morning surveys, and their sleep was measured via actigraphy over 2 school-weeks and 2 subsequent vacation-weeks. Morning surveys assessed self-reported sleep and the usage of 8 facilitators and 6 barriers of sleep from the previous night. Linear mixed-effects models were used to examine contributions of facilitators/barriers to actigraphy and self-reported total sleep time (TST) and sleep onset latency (SOL), controlling for age, sex, race, place of birth, and study day, separately for school and non-school days. Results: On average, adolescents reported using 3.7 facilitators and encountering 1.5 barriers daily. Compared to school, non-school days were characterised by more frequent use of facilitators and more barriers encountered. Overall, facilitators or barriers explained an additional 1–7% (p-values < .01) of variance beyond the covariates. Similar facilitators and barriers contributed to actigraphy and self-reported TST and SOL, however, self-reported sleep variables were more affected. Notable facilitators that predicted longer TST and shorter SOL were: "follow body cues", "avoid activities interfering with sleep", "create good sleep environment", "plan bedtime and go to bed as planned" (only TST on school days), and "manage thoughts and emotions" (only SOL). Notable barriers that predicted shorter TST and longer SOL were: "pre-bedtime thoughts and emotions", "inconsistent routines", "unconducive sleep environment", "activities interfering with sleep" (only non-school) and "other household members' activities" (only SOL). Conclusion: This intense longitudinal study showed that on a daily basis, adolescents perceive a range of factors as facilitating and preventing sufficient and good quality sleep. These factors are predictive of their actual sleep duration and onset latency and need further research to understand their functions and clinical implications. Support (if any):